2018
DOI: 10.1152/ajplung.00557.2017
|View full text |Cite
|
Sign up to set email alerts
|

The vagal ganglia transcriptome identifies candidate therapeutics for airway hyperreactivity

Abstract: Mainstay therapeutics are ineffective in some people with asthma, suggesting a need for additional agents. In the current study, we used vagal ganglia transcriptome profiling and connectivity mapping to identify compounds beneficial for alleviating airway hyperreactivity (AHR). As a comparison, we also used previously published transcriptome data from sensitized mouse lungs and human asthmatic endobronchial biopsies. All transcriptomes revealed agents beneficial for mitigating AHR; however, only the vagal gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 93 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…Consistent with this, a critical role for afferent and efferent airway nerves in the manifestation of asthma features has been increasingly established (6,55,56,62,63). Specific afferent contributors include the transient receptor potential vanilloid 1 (TRPV1) (65), the acid-sensing ion channel (ASIC) 1a (55), the sodium voltagegated ␣-subunit 10 (scn10a/Nav1.8) (63), and the transient receptor potential cation channel, subfamily A, member 1 (TRPA1) (10). A major efferent contributor is cholinergic transmission (56).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Consistent with this, a critical role for afferent and efferent airway nerves in the manifestation of asthma features has been increasingly established (6,55,56,62,63). Specific afferent contributors include the transient receptor potential vanilloid 1 (TRPV1) (65), the acid-sensing ion channel (ASIC) 1a (55), the sodium voltagegated ␣-subunit 10 (scn10a/Nav1.8) (63), and the transient receptor potential cation channel, subfamily A, member 1 (TRPA1) (10). A major efferent contributor is cholinergic transmission (56).…”
Section: Introductionmentioning
confidence: 67%
“…For example, using an adult guinea pig model of gastroesophageal reflux, Hamamoto et al (27) found that esophageal acid caused release of substance P in the lung. Consistent with this, a critical role for afferent and efferent airway nerves in the manifestation of asthma features has been increasingly established (6,55,56,62,63). Specific afferent contributors include the transient receptor potential vanilloid 1 (TRPV1) (65), the acid-sensing ion channel (ASIC) 1a (55), the sodium voltagegated ␣-subunit 10 (scn10a/Nav1.8) (63), and the transient receptor potential cation channel, subfamily A, member 1 (TRPA1) (10).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…pPCLS were made as previously described (Reznikov, Meyerholz, Abou Alaiwa, et al, 2018). Briefly, the porpoise lobe was dissected, cannulated, and insufflated with 2% (weight/vol) low‐melting‐point agarose (Invitrogen) in the culture medium.…”
Section: Methodsmentioning
confidence: 99%